Capital in the twenty-first century [compact disc, unabridged] - Piketty, Thomas, 1971- (Brilliance Audio, Inc., 2014)
Thomas Piketty analyzes a unique collection of data from twenty countries, ranging as far back as the eighteenth century, to uncover key economic and social patterns. His findings will transform debate and set the agenda for the next generation of thought about wealth and inequality.